2021
DOI: 10.22270/jddt.v11i5-s.5068
|View full text |Cite
|
Sign up to set email alerts
|

4D Printing: The Dawn of “Smart” Drug Delivery Systems and Biomedical Applications

Abstract: With the approval of first 3D printed drug “spritam” by USFDA, 3D printing is gaining acceptance in healthcare, engineering and other aspects of life. Taking 3D printing towards the next step gives birth to what is referred to as “4D printing”. The full credit behind the unveiling of 4D printing technology in front of the world goes to Massachusetts Institute of Technology (MIT), who revealed “time” in this technology as the fourth dimension.  4D printing is a renovation of 3D printing wherein special material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Khan et al demonstrated a smart way of fabricating 4D printed microneedles with barbs that curve in response to curing. This backward bending of the barbed structure as shown in figure 8(d) allows for better drug delivery [237]. Similarly, Han et al printed microneedles with reversed barb structures that demonstrated 18 fold increase in the adhesion of microneedles [235].…”
Section: Fabrication Of Mnamentioning
confidence: 90%
See 1 more Smart Citation
“…Khan et al demonstrated a smart way of fabricating 4D printed microneedles with barbs that curve in response to curing. This backward bending of the barbed structure as shown in figure 8(d) allows for better drug delivery [237]. Similarly, Han et al printed microneedles with reversed barb structures that demonstrated 18 fold increase in the adhesion of microneedles [235].…”
Section: Fabrication Of Mnamentioning
confidence: 90%
“…(d) Schematic illustration of 4D printing approach to program deformation of horizontally printed barbs into a backward-facing shape. Reproduced with permission from [237]. CC BY-NC 4.0.…”
Section: Fabrication Of Mnamentioning
confidence: 99%